Method for preparing expanded graphite / silver composite material through microwave expansion

The graphite and silver ions are synchronized by acid treatment and microwave expansion technology to prepare expanded graphite/silver composites with high specific surface area and conductivity, which solves the problems of high preparation costs and poor product stability in the prior art, and realizes efficient preparation and wide application of materials.

CN119569051AInactive Publication Date: 2025-03-07ANHUI BONDRUI NEW MATERIAL TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411752379.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing methods for preparing expanded graphite have problems such as high electrochemical cost, high power consumption, and poor stability of mixed liquid phase products, which limits the wide application of expanded graphite in new energy and environmental protection fields.

Method used

After acid treatment of graphite, it is mixed with silver nitrate solution and synchronized by microwave expansion technology to prepare an expanded graphite/silver composite material to improve its specific surface area and conductivity.

Benefits of technology

A expanded graphite/silver composite material with high specific surface area and excellent conductivity is achieved, which simplifies the preparation process, reduces production costs, and improves the stability and application potential of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569051A_ABST
    Figure CN119569051A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of functional composite material preparation, and particularly relates to a method for preparing an expanded graphite / silver composite material through microwave expansion, and the method comprises the following steps: soaking graphite in an acid solution for oxidation treatment and heating, and then cleaning the graphite with deionized water until the solution is neutral to obtain graphite subjected to acid treatment; the preparation method comprises the following steps: mixing graphite subjected to acid treatment with an AgNO3 solution, uniformly stirring, then carrying out ultrasonic treatment, enabling the graphite to be uniformly infiltrated by the AgNO3 solution, carrying out freeze drying treatment on the mixture, baking the treated material under an infrared lamp, carrying out microwave expansion treatment on the baked mixture, cooling a product subjected to microwave expansion treatment, and carrying out tubular furnace pyrolysis, thereby obtaining the AgNO3 / AgNO3 composite material. And cooling to obtain the expanded graphite / silver composite material. The product obtained by the method disclosed by the invention has relatively high specific surface area and excellent conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional composite material preparation, and in particular relates to a method for preparing expanded graphite / silver composite material by microwave expansion. Background Art

[0002] Expanded graphite, as a new functional carbon material, is a loose and porous worm-like substance obtained by intercalation, washing, drying, high-temperature expansion and other processes of natural graphite flakes. It not only has the excellent properties of natural graphite itself, such as resistance to cold and heat, corrosion resistance, and self-lubrication, but also exhibits the characteristics of softness, compression resilience, adsorption, ecological environment coordination and biocompatibility that natural graphite does not have.

[0003] Although the preparation method of expanded graphite has made significant progress, the existing preparation method still has some defects, such as the electrochemical method requires complex electrolysis equipment and operation, the cost is high, and a large amount of electric energy is consumed during the preparation process, which increases the production cost. Although the mixed liquid phase method has a simple reaction process and a fast reaction speed, the product formed has poor stability and is prone to structural changes during subsequent processing. With the rapid development of industries such as new energy, environmental protection, and electronic information, the demand for high-performance graphite materials is growing. Expanded graphite has broad application prospects in these fields due to its unique structure and performance advantages. However, the limitations of the existing preparation method limit the further development and application of expanded graphite. Therefore, it is of great significance to develop a method for preparing expanded graphite that can overcome the defects of the prior art and achieve high conductivity and specific surface area, which is of great significance for promoting the upgrading and development of the graphite material industry. Summary of the invention

[0004] The present invention provides a method for preparing an expanded graphite / silver composite material. The method comprises the steps of acid-treating graphite, mixing the graphite with a silver nitrate solution, and simultaneously treating the graphite with a microwave expansion technology to obtain an expanded graphite and silver composite material, wherein the obtained product has a high specific surface area and excellent electrical conductivity.

[0005] The technical solution provided by the present invention is as follows:

[0006] A method for preparing expanded graphite / silver composite material by microwave expansion, comprising the following steps: immersing graphite in an acid solution for oxidation treatment and heating, then washing the graphite with deionized water until the solution is neutral to obtain acid-treated graphite; mixing the acid-treated graphite with a AgNO3 solution, stirring evenly and then performing ultrasonic treatment to allow the AgNO3 solution to evenly infiltrate the graphite, freeze-drying the mixture, baking the treated material under an infrared lamp, expanding the baked mixture with microwaves, cooling the product after the microwave expansion treatment, and performing pyrolysis in a tubular furnace to obtain the expanded graphite / silver composite material after cooling.

[0007] Further, the acid-treated graphite is mixed with the AgNO3 solution, stirred evenly and then subjected to ultrasonic treatment. After the ultrasonic treatment, the mixture is subjected to high-speed shear grinding for 1 to 2 hours using a colloid mill, and the rotation speed of the colloid mill is 3500 to 5000 r / min.

[0008] Furthermore, the pyrolysis is to place the cooled microwave expansion product into a tubular furnace, heat it to 850-1000°C at a heating rate of 6-9°C / min under the protection of nitrogen, and pyrolyze it at a constant temperature for 1-2h, and obtain the expanded graphite / silver composite material after cooling.

[0009] Furthermore, the acid solution is one or more of concentrated sulfuric acid, concentrated nitric acid, and perchloric acid, and the concentration of the acid solution is above 70% v / v.

[0010] Furthermore, the graphite is immersed in an acid solution for oxidation treatment and heated at a heating concentration of 100 to 200° C. for a heating time of 10 minutes to 2 hours.

[0011] Furthermore, the mass ratio of silver ions to graphite in the AgNO3 solution is 2:3-5; the AgNO3 solution is prepared by dissolving AgNO3 in a water / ethanol mixed solution, and the volume ratio of water to ethanol is 2:1-3.

[0012] The baking temperature is 60-80°C and the time is 2h.

[0013] The microwave expansion treatment is an interval microwave treatment, the power of the microwave treatment is 600-1000W, the microwave treatment is 20-30s, and the pause is 10-20s, and the total treatment time is 3-5min.

[0014] A method for preparing an expanded graphite / silver composite material by microwave expansion comprises the following steps:

[0015] The invention also provides an expanded graphite / silver composite material, which is prepared by the method.

[0016] The present invention also provides application of the expanded graphite / silver composite material in preparing an electrochemical energy storage device.

[0017] Beneficial Effects

[0018] Acid treatment can effectively remove impurities and oxides from graphite, improve its purity, and exfoliate graphite flakes, increasing its specific surface area and active sites, thereby helping to reduce electron scattering and traps in graphite and improving its conductivity. The introduction of metal ions can affect the charge transfer in graphite, thereby improving its conductivity. Metal ions generally have higher electrical conductivity than carbon, so their presence can form more conductive channels and promote the transmission of electrons in graphite. The introduction of metal ions can also enhance the thermal stability of graphite and extend the service life of graphite.

[0019] The microwave expansion method is based on the conductive properties of graphite. It uses the magnetic waves generated by the magnetron to generate strong eddy currents inside the graphite, which in turn causes the expandable graphite to heat up rapidly from the inside out. This heating method allows the polar molecules between the graphite layers to interact with the microwaves, causing the compounds inserted between the graphite layers to decompose and vaporize rapidly to form expanded graphite. Since the heating is rapid and uniform, the internal structure of the graphite is maintained, so its conductive properties are retained. Microwave expansion treatment can optimize the internal structure of graphite, giving it more conductive channels and lower resistance, thereby improving the conductive efficiency. Microwave expansion treatment causes graphite to peel along the C axis to form expanded graphite. This structural change gives graphite more pores and a larger specific surface area, thereby increasing the transmission path and contact area of ​​electrons in graphite. At the same time, the expansion treatment can also remove some impurities and defects in the graphite, further reducing resistance and improving conductive efficiency.

[0020] After graphite is treated with acid by the method of the present invention, silver particles are simultaneously introduced during microwave expansion. The preparation process of the composite material is simplified by synchronous microwave expansion and deposition of silver particles, and the complex steps in the traditional chemical reduction process are reduced. A rotating tray is used during microwave expansion to ensure the uniformity of microwave field distribution and improve the uniformity and consistency of the composite powder material. The expanded graphite / silver composite material obtained by the method of the present invention has a high specific surface area, excellent electrical conductivity and good catalytic activity, and can be widely used in electrochemical energy storage devices (such as supercapacitors, batteries), conductive coatings, conductive inks, catalyst carriers and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the expanded graphite / silver composite material obtained in Example 1 of the present invention.

[0022] Figure 2 This is a SEM image of the expanded graphite / silver composite material obtained in Example 2 of the present invention. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A method for preparing an expanded graphite / silver composite material by microwave expansion comprises the following steps:

[0026] 1. Graphite acid treatment: Graphite is immersed in an acid solution for oxidation treatment and heated at a temperature of 150°C for 1 hour to increase the interlayer spacing of graphite and to provide expansion characteristics. The graphite is then washed with deionized water until the solution is neutral to obtain acid-treated graphite. The acid solution is a mixture of concentrated nitric acid and perchloric acid, with a volume ratio of concentrated nitric acid (70% v / v) to perchloric acid (70% v / v) of 2:1.

[0027] 2. Prepare a silver nitrate (AgNO3) solution by dissolving AgNO3 in a water / ethanol mixed solution with a volume ratio of water to ethanol of 1:1. Adjust the concentration of AgNO3 so that the mass ratio of silver ions to graphite is 1:2.

[0028] 3. Mix the acid-treated graphite with the AgNO3 solution, stir evenly and then perform ultrasonic treatment. After ultrasonic treatment, use a colloid mill to perform high-speed shear grinding for 1 hour at a speed of 3500r / min to make the AgNO3 solution evenly infiltrate the graphite. Freeze-dry the mixture and bake the treated material under an infrared lamp at a temperature of 70°C for 2 hours to ensure that the solvent in the solution is fully evaporated.

[0029] 4. Microwave expansion treatment: The baked mixture is transferred to a microwave oven for expansion treatment. The power of the microwave oven is set to 800W, and the treatment time is 4 minutes. The microwave expansion treatment is an interval microwave treatment, the power of the microwave treatment is 800W, the microwave treatment is 20s, and the pause is 1s, and the total treatment time is 4min. A rotating tray is used to keep the sample heated evenly to ensure the rapid expansion of graphite and the uniform distribution of Ag during microwave heating. During the expansion process, AgNO3 is reduced to generate metallic silver particles, which are distributed on the surface or inside of the expanded graphite.

[0030] 5. Cool the microwave expanded product and perform pyrolysis in a tubular furnace to obtain an expanded graphite / silver composite material (EG / Ag) after cooling. The pyrolysis is to place the cooled microwave expanded product in a tubular furnace, heat it to 900°C at a heating rate of 8°C / min under the protection of nitrogen, and pyrolyze it at a constant temperature for 2h, and obtain the expanded graphite / silver composite material after cooling.

[0031] Example 2

[0032] A method for preparing an expanded graphite / silver composite material by microwave expansion comprises the following steps:

[0033] 1. Graphite acid treatment: Graphite is immersed in an acid solution for oxidation treatment and heated at a temperature of 150°C for 1 hour to increase the interlayer spacing of graphite and provide expansion characteristics. The graphite is then washed with deionized water until the solution is neutral to obtain acid-treated graphite. The acid solution is concentrated nitric acid (70% v / v).

[0034] 2. Prepare a silver nitrate (AgNO3) solution by dissolving AgNO3 in a water / ethanol mixed solution with a volume ratio of water to ethanol of 1:1. Adjust the concentration of AgNO3 so that the mass ratio of silver ions to graphite is 1:2.

[0035] 3. Mix the acid-treated graphite with the AgNO3 solution, stir evenly and then perform ultrasonic treatment. After ultrasonic treatment, use a colloid mill to perform high-speed shear grinding for 1 hour at a speed of 3500r / min to make the AgNO3 solution evenly infiltrate the graphite. Freeze-dry the mixture and bake the treated material under an infrared lamp at a temperature of 70°C for 2 hours to ensure that the solvent in the solution is fully evaporated.

[0036] 4. Microwave expansion treatment: The baked mixture is transferred to a microwave oven for expansion treatment. The power of the microwave oven is set to 800W, and the treatment time is 4 minutes. The microwave expansion treatment is an interval microwave treatment, the power of the microwave treatment is 800W, the microwave treatment is 20s, and the pause is 1s, and the total treatment time is 4min. A rotating tray is used to keep the sample heated evenly to ensure the rapid expansion of graphite and the uniform distribution of Ag during microwave heating. During the expansion process, AgNO3 is reduced to generate metallic silver particles, which are distributed on the surface or inside of the expanded graphite.

[0037] 5. Cool the microwave expanded product and perform pyrolysis in a tubular furnace to obtain an expanded graphite / silver composite material (EG / Ag) after cooling. The pyrolysis is to place the cooled microwave expanded product in a tubular furnace, heat it to 900°C at a heating rate of 8°C / min under the protection of nitrogen, and pyrolyze it at a constant temperature for 2h, and obtain the expanded graphite / silver composite material after cooling.

[0038] Example 3

[0039] A method for preparing an expanded graphite / silver composite material by microwave expansion comprises the following steps:

[0040] 1. Graphite acid treatment: Graphite is immersed in an acid solution for oxidation treatment and heated at a temperature of 150°C for 1 hour to increase the interlayer spacing of graphite and to provide expansion characteristics. The graphite is then washed with deionized water until the solution is neutral to obtain acid-treated graphite. The acid solution is concentrated sulfuric acid (70% v / v).

[0041] 2. Prepare a silver nitrate (AgNO3) solution by dissolving AgNO3 in a water / ethanol mixed solution with a volume ratio of water to ethanol of 1:1. Adjust the concentration of AgNO3 so that the mass ratio of silver ions to graphite is 1:2.

[0042] 3. Mix the acid-treated graphite with the AgNO3 solution, stir evenly and then perform ultrasonic treatment. After ultrasonic treatment, use a colloid mill to perform high-speed shear grinding for 1 hour at a speed of 3500r / min to make the AgNO3 solution evenly infiltrate the graphite. Freeze-dry the mixture and bake the treated material under an infrared lamp at a temperature of 70°C for 2 hours to ensure that the solvent in the solution is fully evaporated.

[0043] 4. Microwave expansion treatment: The baked mixture is transferred to a microwave oven for expansion treatment. The power of the microwave oven is set to 800W, and the treatment time is 4 minutes. The microwave expansion treatment is an interval microwave treatment, the power of the microwave treatment is 800W, the microwave treatment is 20s, and the pause is 1s, and the total treatment time is 4min. A rotating tray is used to keep the sample heated evenly to ensure the rapid expansion of graphite and the uniform distribution of Ag during microwave heating. During the expansion process, AgNO3 is reduced to generate metallic silver particles, which are distributed on the surface or inside of the expanded graphite.

[0044] 5. Cool the microwave expanded product and perform pyrolysis in a tubular furnace to obtain an expanded graphite / silver composite material (EG / Ag) after cooling. The pyrolysis is to place the cooled microwave expanded product in a tubular furnace, heat it to 900°C at a heating rate of 8°C / min under the protection of nitrogen, and pyrolyze it at a constant temperature for 2h, and obtain the expanded graphite / silver composite material after cooling.

[0045] Example 4

[0046] A method for preparing an expanded graphite / silver composite material by microwave expansion comprises the following steps:

[0047] 1. Graphite acid treatment: Graphite is immersed in an acid solution for oxidation treatment and heated at a temperature of 150°C for 1 hour to increase the interlayer spacing of graphite and to provide expansion characteristics. The graphite is then washed with deionized water until the solution is neutral to obtain acid-treated graphite. The acid solution is perchloric acid (70% v / v).

[0048] 2. Prepare a silver nitrate (AgNO3) solution by dissolving AgNO3 in a water / ethanol mixed solution with a volume ratio of water to ethanol of 1:1. Adjust the concentration of AgNO3 so that the mass ratio of silver ions to graphite is 1:2.

[0049] 3. Mix the acid-treated graphite with the AgNO3 solution, stir evenly and then perform ultrasonic treatment. After ultrasonic treatment, use a colloid mill to perform high-speed shear grinding for 1 hour at a speed of 3500r / min to make the AgNO3 solution evenly infiltrate the graphite. Freeze-dry the mixture and bake the treated material under an infrared lamp at a temperature of 70°C for 2 hours to ensure that the solvent in the solution is fully evaporated.

[0050] 4. Microwave expansion treatment: The baked mixture is transferred to a microwave oven for expansion treatment. The power of the microwave oven is set to 800W, and the treatment time is 4 minutes. The microwave expansion treatment is an interval microwave treatment, the power of the microwave treatment is 800W, the microwave treatment is 20s, and the pause is 1s, and the total treatment time is 4min. A rotating tray is used to keep the sample heated evenly to ensure the rapid expansion of graphite and the uniform distribution of Ag during microwave heating. During the expansion process, AgNO3 is reduced to generate metallic silver particles, which are distributed on the surface or inside of the expanded graphite.

[0051] 5. Cool the microwave expanded product and perform pyrolysis in a tubular furnace to obtain an expanded graphite / silver composite material (EG / Ag) after cooling. The pyrolysis is to place the cooled microwave expanded product in a tubular furnace, heat it to 900°C at a heating rate of 8°C / min under the protection of nitrogen, and pyrolyze it at a constant temperature for 2h, and obtain the expanded graphite / silver composite material after cooling.

[0052] Example 5

[0053] A method for preparing an expanded graphite / silver composite material by microwave expansion comprises the following steps:

[0054] 1. Graphite acid treatment: Graphite is immersed in an acid solution for oxidation treatment and heated at a temperature of 150°C for 1 hour to increase the interlayer spacing of graphite and to provide expansion characteristics. The graphite is then washed with deionized water until the solution is neutral to obtain acid-treated graphite. The acid solution is a mixture of concentrated nitric acid and perchloric acid, with a volume ratio of concentrated nitric acid (70% v / v) to perchloric acid (70% v / v) of 1:2.

[0055] 2. Prepare a silver nitrate (AgNO3) solution by dissolving AgNO3 in a water / ethanol mixed solution with a volume ratio of water to ethanol of 1:1. Adjust the concentration of AgNO3 so that the mass ratio of silver ions to graphite is 1:2.

[0056] 3. Mix the acid-treated graphite with the AgNO3 solution, stir evenly and then perform ultrasonic treatment. After ultrasonic treatment, use a colloid mill to perform high-speed shear grinding for 1 hour at a speed of 3500r / min to make the AgNO3 solution evenly infiltrate the graphite. Freeze-dry the mixture and bake the treated material under an infrared lamp at a temperature of 70°C for 2 hours to ensure that the solvent in the solution is fully evaporated.

[0057] 4. Microwave expansion treatment: The baked mixture is transferred to a microwave oven for expansion treatment. The power of the microwave oven is set to 800W, and the treatment time is 4 minutes. The microwave expansion treatment is an interval microwave treatment, the power of the microwave treatment is 800W, the microwave treatment is 20s, and the pause is 1s, and the total treatment time is 4min. A rotating tray is used to keep the sample heated evenly to ensure the rapid expansion of graphite and the uniform distribution of Ag during microwave heating. During the expansion process, AgNO3 is reduced to generate metallic silver particles, which are distributed on the surface or inside of the expanded graphite.

[0058] 5. Cool the microwave expanded product and perform pyrolysis in a tubular furnace to obtain an expanded graphite / silver composite material (EG / Ag) after cooling. The pyrolysis is to place the cooled microwave expanded product in a tubular furnace, heat it to 900°C at a heating rate of 8°C / min under the protection of nitrogen, and pyrolyze it at a constant temperature for 2h, and obtain the expanded graphite / silver composite material after cooling.

[0059] Comparative Example 1

[0060] The difference between this comparative example and Example 1 is that the graphite is not subjected to acid treatment, and the other conditions remain unchanged.

[0061] Comparative Example 2

[0062] The difference between this comparative example and Example 1 is that no AgNO3 solution is used, and the other conditions remain unchanged.

[0063] Comparative Example 3

[0064] The difference between this comparative example and Example 1 is that no ultrasonic treatment was performed, and the other conditions remained unchanged.

[0065] Comparative Example 4

[0066] The difference between this comparative example and Example 1 is that no colloid mill treatment is used, and the other conditions remain unchanged.

[0067] Comparative Example 5

[0068] The difference between this comparative example and Example 1 is that freeze drying treatment is not adopted, and other conditions remain unchanged.

[0069] Comparative Example 6

[0070] The difference between this comparative example and Example 1 is that microwave expansion treatment is not adopted, and other conditions remain unchanged.

[0071] Comparative Example 7

[0072] The difference between this comparative example and Example 1 is that the microwave expansion treatment is carried out continuously without using interval microwave treatment, and the other conditions remain unchanged.

[0073] Comparative Example 8

[0074] The difference between this comparative example and Example 1 is that no tubular furnace pyrolysis is used, and the other conditions remain unchanged.

[0075] Test Example 1

[0076] The electrical conductivity of the products prepared in the examples and comparative examples was tested.

[0077]

[0078] As can be seen from the above results, the present invention treats graphite with acid and adds silver ions, and the introduction of metal ions can affect the charge transfer in graphite, thereby improving its conductivity. Metal ions usually have a higher conductivity than carbon, so their presence can form more conductive channels and promote the transmission of electrons in graphite. After that, microwave expansion treatment is performed, and the graphite is expanded by utilizing the high-energy microwave effect. The appropriate expansion can widen the interlayer spacing of the graphite, thereby improving its conductivity.

[0079] Test Example 2

[0080] The performance tests were performed on the products prepared in the examples and comparative examples. The specific test methods and test results are as follows:

[0081] The products obtained in each embodiment or comparative example were mixed with conductive carbon black and polyvinylidene fluoride binder in a mass ratio of 8:1:1, and N-methylpyrrolidone was added. After grinding, they were coated on the surface of a copper foil with a thickness of 6 μm, and dried as a working electrode;

[0082] The metal lithium sheet, working electrode, PP separator, and 1 mol / L LiPF6 electrolyte were assembled into a CR2032 button cell, and the battery assembly was carried out in a glove box filled with argon protection;

[0083] The button cell was tested for charge, discharge and cycle performance using a LAND test system (LAND CT2001A). The voltage test range was 0.01-3.0V. For the same example or comparative example product, multiple groups of tests were conducted. The charge and discharge current densities were adjusted to 0.1C and 0.3C, respectively. After 40 cycles of charge and discharge, the capacity retention rate of each battery was tested. The specific test results are shown in the following table:

[0084]

[0085] From the above results, it can be seen that the product obtained by the method of the present invention has a good capacity retention rate during the charge and discharge process. In particular, when the charge rate is increased, the capacity retention rate decreases relatively less, which can meet the demand for high-rate charge and discharge.

[0086] Test Example 3

[0087] The specific surface area of ​​the products in the embodiments and comparative examples was tested according to the test method in the standard GB / T-24533-2019 "Graphite Anode Materials for Lithium Ion Batteries", and the powder OI value and interlayer spacing thereof were tested by XRD; the test results are shown in the following table:

[0088]

[0089]

[0090] It can be seen from the above table that the expanded graphite / silver composite material prepared by the method of the present invention has a good specific surface area and interlayer spacing.

[0091] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0092] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing expanded graphite / silver composite material by microwave expansion, characterized in that: The method comprises the following steps: immersing graphite in an acid solution for oxidation treatment and heating, then washing the graphite with deionized water until the solution is neutral to obtain acid-treated graphite; mixing the acid-treated graphite with a AgNO3 solution, stirring evenly and then performing ultrasonic treatment to allow the AgNO3 solution to evenly infiltrate the graphite, performing freeze-drying treatment on the mixture, baking the treated material under an infrared lamp, performing microwave expansion treatment on the baked mixture, cooling the product after the microwave expansion treatment, and performing pyrolysis in a tubular furnace to obtain an expanded graphite / silver composite material after cooling.

2. The method for preparing expanded graphite / silver composite material by microwave expansion according to claim 1, characterized in that: The acid-treated graphite is mixed with the AgNO3 solution, stirred evenly and then subjected to ultrasonic treatment. After the ultrasonic treatment, the mixture is subjected to high-speed shear grinding for 1 to 2 hours using a colloid mill, and the rotation speed of the colloid mill is 3500 to 5000 r / min.

3. The method for preparing expanded graphite / silver composite material by microwave expansion according to claim 1, characterized in that: The pyrolysis comprises placing the cooled microwave expansion product into a tubular furnace, heating it to 850-1000° C. at a heating rate of 6-9° C. / min under the protection of nitrogen, and pyrolyzing it at a constant temperature for 1-2 hours, and obtaining the expanded graphite / silver composite material after cooling.

4. The method for preparing expanded graphite / silver composite material by microwave expansion according to claim 1, characterized in that: The acid solution is one or more of concentrated sulfuric acid, concentrated nitric acid and perchloric acid, and the concentration of the acid solution is above 70% v / v.

5. The method for preparing expanded graphite / silver composite material by microwave expansion according to claim 1, characterized in that: The graphite is immersed in an acid solution for oxidation treatment and heated at a heating concentration of 100 to 200° C. for a heating time of 10 minutes to 2 hours.

6. The method for preparing expanded graphite / silver composite material by microwave expansion according to claim 1, characterized in that: The mass ratio of silver ions to graphite in the AgNO3 solution is 2:3-5; the AgNO3 solution is prepared by dissolving AgNO3 in a water / ethanol mixed solution, and the volume ratio of water to ethanol is 2:1-3.

7. The method for preparing expanded graphite / silver composite material by microwave expansion according to claim 1, characterized in that: The baking temperature is 60-80°C and the time is 2h.

8. The method for preparing expanded graphite / silver composite material by microwave expansion according to claim 1, characterized in that: The microwave expansion treatment is an interval microwave treatment, the power of the microwave treatment is 600-1000W, the microwave treatment is 20-30s, and the pause is 10-20s, and the total treatment time is 3-5min.

9. An expanded graphite / silver composite material, characterized in that: The invention is prepared by the method according to any one of claims 1 to 8.

10. Use of the expanded graphite / silver composite material according to claim 9 in the preparation of an electrochemical energy storage device.

Citation Information

Patent Citations

  • Silver / graphene compound material and application

    CN102698747A

  • Method for electrochemically preparing graphene

    CN102807213A

  • Preparation method and application of composite material of expanded graphite in-situ growth silver nanoparticles

    CN114195146A

  • Expanded graphite-silver composite negative electrode material and preparation method thereof

    CN115224256A

  • Expanded graphite supporting NiB amorphous alloy catalyst, its preparation method and application

    CN1768932A